2015
DOI: 10.1002/ange.201411297
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Concise Biosynthetic Pathway of the Communesin Indole Alkaloids

Abstract: The communesins are a prominent class of indole alkaloids isolated from Penicillium species. Owing to their daunting structural framework and potential as pharmaceuticals, communesins have inspired numerous synthetic studies. However, the genetic and biochemical basis of communesin biosynthesis has remained unexplored. Herein, we report the identification and characterization of the communesin (cns) biosynthetic gene cluster from Penicillium expansum. We confirmed that communesin is biosynthesized by the coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 34 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The absolute configuration was determined to be R by the enantioselective total synthesis by Stoltz et al . (−)‐Aurantioclavine is a biosynthetic intermediate of communesins, complex polycyclic alkaloids with various bioactivities . (−)‐Aurantioclavine is therefore an attractive target for synthetic organic and medicinal chemists.…”
Section: Application Of the Developed Methods To The Synthesis Of Natmentioning
confidence: 99%
“…The absolute configuration was determined to be R by the enantioselective total synthesis by Stoltz et al . (−)‐Aurantioclavine is a biosynthetic intermediate of communesins, complex polycyclic alkaloids with various bioactivities . (−)‐Aurantioclavine is therefore an attractive target for synthetic organic and medicinal chemists.…”
Section: Application Of the Developed Methods To The Synthesis Of Natmentioning
confidence: 99%
“…Penicillium camemberti accumulates N‐methyl‐DMAT (requiring only the genes dmaW and easF ) under certain culture conditions but not in cheese (Fabian et al, 2018). Lin et al (2015) showed that genes cnsF (a homologue of dmaW ), cnsA (a homologue of easE ) and cnsD (a homologue of easC ) from Penicillium expansum can synthesize aurantioclavine. These three genes represent the enzyme complement required for chanoclavine‐I biosynthesis minus the N‐methyl transferase encoded by easF .…”
Section: Accumulation Of Products From the Basal Portion Of The Pathwaymentioning
confidence: 99%
“…These three genes represent the enzyme complement required for chanoclavine‐I biosynthesis minus the N‐methyl transferase encoded by easF . Aurantioclavine may then be coupled with tryptamine derivatives to produce the complex family of communesins (Lin et al, 2015).…”
Section: Accumulation Of Products From the Basal Portion Of The Pathwaymentioning
confidence: 99%